Perlindungan Hak Individu Melalui Pendekatan Lex Favor Reo Di Sistem Hukum Pidana - Nadhir, Khibran; Firmansyah, Hery (Universitas Ekasakti, 2023)
Individual rights are the personal rights of Indonesian citizens in the eyes of the law, including within the criminal law system. The criminal law system in Indonesia recognizes